Care Management for Youth With Comorbid Developmental and Mental Health Conditions: A Discrete Choice Experiment Pilot Study - dosReis, Susan; N'Dri, Laetitia; Ross, Melissa; Camelo Castillo, Wendy; Reeves, Gloria; Butler, Beverly (Academic pediatrics, 2020)
Caregivers of a child with a coexisting cognitive/intellectual and an emotional/behavior/developmental disability have difficult decisions regarding care management options for their child. This study aimed to pilot and refine an instrument to elicit caregivers’ preferences in managing their child's care needs. Subjects were 38 caregivers of a child aged 21 and younger with a coexisting cognitive/intellectual and an emotional/behavior/developmental disability. A mixed-methods design was used to develop and pilot a discrete choice experiment (DCE) to elicit care management preferences for their child. Six attributes of care management decisions were tested in the DCE: medication use, parental custody, time cost, social interactions, medication effects, and school placement. Subjects completed a paper-and-pencil survey after which a debriefing discussion was held to obtain feedback that would aid in refining the attribute descriptions. Conditional logistic regression generated mean scores for each attribute. Comments from the debriefing sessions were audio-recorded and used to modify the attribute descriptions. The majority (84%) of subjects were aged 40 years or older and a female caregiver. Common diagnoses of the children were autism spectrum disorder (55%) and attention-deficit/hyperactivity disorder (76%). Subjects preferred using fewer medications and maintaining decision-making authority as opposed to delegating authority to a third party. Medication effects on the child's mood were more important than effects on personality or body weight. The DCE was sensitive to caregivers’ preferences for managing their child's coexisting cognitive/intellectual and emotional/behavior/developmental disability. Findings may help providers gauge treatment in a broader context of health outcomes.